Environmental offering and coffee cup quality (Coffea arabica L.) Var. Castillo in southern Colombia - Claudia Patricia Criollo-Velásquez; Johana Alixa Muñoz-Belalcazar; Tulio César Lagos-Burbano (Revista de Ciencias Agrícolas, 2020)
The determinant factors of coffee cup quality are highly variable and depend on their interaction with coffee production and benefit. This study aimed to analyze soil and climatic factors and their association with the cup quality of Castillo coffee variety of three to five years of age from production units in ecotypes 220A and 221A of the Department of Nariño. The study farms were located in three different altitudinal ranges: ≤1500 m, between 1501 and 1700 m, and >1700 m. Soil, climate, and coffee cup quality variables were analyzed through principal component analysis and cluster analysis. A low level of association was found between climatic and soil nutritional factors and coffee cup quality. Soil Mn, Fe, and Cu contents showed the highest association levels with cup quality, indicated by an average score of 80.89. The highest values of photosynthetically active radiation -PAR- and thermal amplitude were found in La Unión - Nariño, and these variables were associated with the group that obtained the highest cup quality score (82.58). Cup quality was not associated with elevation since the highest scores (85.5 and 82.33) were obtained from production units located at ≤1500 m.a.s.l. and >1700 m.a.s.l, respectively.